Johanneberg Science Park - Drivkrafterna bakom etableringar i en teknikpark utifrån ett företagsperspektiv - Adam, Abderisak; Ekberg, Dan; Holmquist, Frida; PERNBOM, JOHANNA (My University, 2011)
In a world where business connections are playing a greater part, the role of the traditional science park becomes one of exceeding interest. As industrial firms seek out to develop deeper and more intricate relationships with universities one is forced to ask whether or not the driving forces behind this phenomenon has been adequately mapped out. What are these driving forces and to which degree do they differ depending on the size and the type of the business in question? This bachelor thesis sets out to answer these inquiries by means of a qualitative method involving a limited case study of Johanneberg Science Park and three firms considering relocating to that park. The science park is located in the city of Gothenburg, Sweden in close proximity to Chalmers University of Technology. The main conclusion of the study is that a science park needs to differentiate between the various driving forces behind each of its tenant’s willingness to relocate to that particular park. Larger firms tend to value the outlooks for specific research projects while smaller firms are content with the ability to recruit personnel as well as the opportunity to house their businesses in proximity to a highly valued brand like that of a university. The study does not go beyond the scope of mapping out these driving forces, instead it focuses on highlighting the different incentives as they relate to each of the tenants. Key words: science parks, driving forces, establishment, Johanneberg Science Park
Keywords: Byggproduktion; Annan samhällsbyggnadsteknik; Innovation och entreprenörskap (nyttiggörande); Företagsekonomi; Building Futures; Construction Management; Other Civil Engineering; Innovation & Entrepreneurship; Business Administration; Building Futures